Analisis Teori Akumulasi Modal Adam Smith Terhadap UMKM di Indonesia (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2024)
The development of a country is influenced by the economic growth that occurs in that country. Adam Smith, one of the classical school of economics figures, describes his thoughts on the economic growth of a country by using the theory of capital accumulation. The need for capital accumulation through savings and capital investment is an important key to economic growth. Capital investment is the best way to maximize profits and generate wealth for people. Fast or slow economic growth is determined by the country's capital accumulation. But in reality, Indonesia which is included in the group of developing countries has a major problem in the form of limited capital in order to increase economic growth in the development process in Indonesia. One sector that plays a role in economic growth and national economic recovery is MSMEs. The contribution of MSMEs is recorded at around 61 percent of Indonesia's national GDP and absorbs 97 percent of the total workforce in Indonesia as of May 20, 2022. One of the obstacles for MSMEs in Indonesia is limited capital, which causes production activities to be hampered and reduce income. In order to help MSMEs to have easy access to capital, the Indonesian government channeled Ultra Micro financing and formulated a National Economic Recovery Program (PEN) policy for MSME Support so that MSME actors could get access to capital easily and equitably.